2019
DOI: 10.1002/jssc.201900106
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive liquid‐liquid microextraction coupled with pressure‐assisted electrokinetic injection for simultaneous enrichment of seven phenolic compounds in water samples followed by determination using capillary electrophoresis

Abstract: Offline dispersive liquid-liquid microextraction combined with online pressureassisted electrokinetic injection was developed to simultaneously enrich seven phenolic compounds in water samples, followed by determination using capillary electrophoresis, namely phenol, 4-chlorophenol, pentachlorophenol, 2,4,6trichlorophenol, 2,4-dichlorophenol, 2-chlorophenol, and 2,6-dichlorophenol. Several parameters affecting separation performance of capillary electrophoresis and the enrichment efficiency of pressure-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…The sorption time upon application of the sorbent studied in the present work is shorter compared to Pt fiber coated with single-walled carbon nanotubes (60 min) [11], poly(vinylpyridineethylene dimethacrylate) monolithic material (120 min) [12], polyacrylate fiber (40 min) [13], MIP (120 min [24], 180 min [58]), magnetic nanoparticles (10 min [31], 20 min [32]), as well as than that using pretreatment method (Supporting information Table S13). Upon application of DLLME-PAEKI-CE, characteristics comparable with the present work were achieved (LOD = 0.03-0.28 μg/L, extraction time = 14 min) [21]; however, MSPE-CE allows one to perform detection in a wider range (0.2-950 μg/L).…”
Section: Performance Comparison With Other Methods For Phenolssupporting
confidence: 82%
See 2 more Smart Citations
“…The sorption time upon application of the sorbent studied in the present work is shorter compared to Pt fiber coated with single-walled carbon nanotubes (60 min) [11], poly(vinylpyridineethylene dimethacrylate) monolithic material (120 min) [12], polyacrylate fiber (40 min) [13], MIP (120 min [24], 180 min [58]), magnetic nanoparticles (10 min [31], 20 min [32]), as well as than that using pretreatment method (Supporting information Table S13). Upon application of DLLME-PAEKI-CE, characteristics comparable with the present work were achieved (LOD = 0.03-0.28 μg/L, extraction time = 14 min) [21]; however, MSPE-CE allows one to perform detection in a wider range (0.2-950 μg/L).…”
Section: Performance Comparison With Other Methods For Phenolssupporting
confidence: 82%
“…DLLME combined with pressure-assisted electrokinetic injection (PAEKI) was developed by Suya Ma et al for simultaneous determination of PL, 4-CP, 2-CP, 2,4,6-trichlorophenol (TCP), and 2,4-DCP. The EF reached values of 61-3288 [21].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…However, when the voltage was too high, the peak shape began to deteriorate, and peak area and peak height began to decrease. This was probably due to the excessive electropercolation pushing the analytes out of the capillary orifice, making the accumulation effect worse (Ma et al, 2019). In addition, it was also observed that, when the voltage was high (>−7 kV), the separation was prone to flow instability and poor repeatability of the targeted analytes.…”
Section: Resultsmentioning
confidence: 99%
“…Different organic, ionic, and deep eutectic solvents (DESs) have been used in liquid phase extraction and microextraction procedures as the extractive media. [12][13][14][15][16][17][18][19][20][21] In the recent years DESs have attracted many attentions due to their expensiveness, easy preparation, high extraction capability, and less toxicity. DES is a homogeneous and clear solution formed by combining hydrogen bond donor (HBD) with hydrogen bond acceptor (HBA) in a certain ratio at the suitable temperature.…”
Section: Introductionmentioning
confidence: 99%